STRATEGY FOR ANTICIPATING VIOLENCE AND INTOLERANCE PRACTICES IN THE SPECIAL REGION OF YOGYAKARTA 2016-2019 - David Efendi; Sanny Nofrima; Herdin Arie Saputra (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Intolerance, discrimination, and violence are three different concepts with different motives and categories, but in the practice of social-society life, the three intersect with each other. This research uses qualitative research with a combination of literature and field studies (mix method). Supported by secondary data processed through the Nvivo 12 Plus analysis to compare alignment using the Nvivo QDA technique, the data is obtained from observations of research subjects using a qualitative data analysis model. To anticipate the practice of violence and intolerance in the Special Region of Yogyakarta, this research becomes a solution to deal with the problems of intolerance that often occur in Yogyakarta. If latent cases have manifested into social conflicts, repressive handling is urgently needed with a practical approach without ignoring human values. Potential acts of intolerance, discrimination, and radicalism in the latent stage can be prevented (preventive) or through guidance and direction activities to influence (persuasive).